Considering the IMF's Perspective on a "Sound Fiscal Policy" - Heller, Peter (Washington, D.C. : International Monetary Fund, 2002)
This paper provides a perspective on how the IMF assesses a 'sound fiscal policy,' focusing principally on industrial and emerging market economies. It observes six central criteria: the short-term fiscal policy stance, with greater emphasis on automatic stabilizers than discretionary fiscal policy; relevance of medium- and sometimes long-term issues; fiscal sustainability; capacity for aggregate fiscal policy implementation (including political economy factors); structural content of fiscal policy (tax efficiency and public expenditure quality); and institutional, governance, and process issues associated with budget implementation and revenue collection. Greater emphasis could be placed on an adequate margin to deal with uncertain long-term challenges.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet